A Graphical Environment for the Semantic Validation of a Plan Execution Language - Rocha, Camilo; Muñoz, Cesar; Cadavid, Hector (© Copyright 2021 IEEE, 2009)
This paper presents PLEXIL5, PLEXIL's formal interacting visual environment, a graphical environment providing an user-friendly interface to the formal operational semantics of PLEXIL. PLEXIL is a synchronous plan execution language developed by NASA to support autonomous space operations. PLEXIL5 serves as a testbed for designers, developers and users of PLEXIL's executive system to validate, maintain, and debug the implementation of the system against the formal semantics of the language. The executable formal semantics of PLEXIL is an executable rewriting logic theory in Maude's language.

Este documento presenta PLEXIL5, el entorno visual interactivo formal de PLEXIL, un entorno gráfico que proporciona una interfaz fácil de usar para la semántica operativa formal de PLEXIL. PLEXIL es un lenguaje de ejecución de planes sincrónicos desarrollado por la NASA para respaldar las operaciones espaciales autónomas. PLEXIL5 sirve como banco de pruebas para diseñadores, desarrolladores y usuarios del sistema ejecutivo de PLEXIL para validar, mantener y depurar la implementación del sistema contra la semántica formal del lenguaje. La semántica formal ejecutable de PLEXIL es una teoría lógica de reescritura ejecutable en el lenguaje de Maude.
Keywords: High level languages; Program verification; Rewriting systems; User interfaces; Sistemas interactivos; PLEXIL5; Ciencias de la Computación; MAUDE; Tecnologías de la información; Lógica; Interfaces de usuario; Sistemas de reescritura; Logic; NASA; Concurrent Computing; Java; Space vehicles; Space missions; Information technology; Computer science; USA Councils; System testing